MINAT BELAJAR SISWA KELAS XI PADA MATA PELAJARAN MENGHIAS BUSANA DI SMK NEGERI 3 SUNGAI PENUH - Wetti, Pera; Ramainas, Ramainas; Ernawati, Ernawati (Journal of Home Economics and Tourism, 2013)
This study begins with a problem lack of student interest in participating subject clothes purpose decorate fashion. This study to describe the class XI student interest in the subject of decorating fashion in SMK N 3 sungai penuh, seen from the factor attention, desires, and feelings. This researsh is a descriptive study in this research quantitative. Population class XI student of the school year 2012 / 2013 amounthing to 37 people, where the entire population of the research sample (sampling Saturated). Techniques of data collection using a likert scale questionnaire from which has been validity and reliable, data analysis was done by using SPSS (Statistic Product Solution Service) version 12. The result showed that the score of student attention enough that category 54,1%Â  while the desire of student including high category that 61,5% and feelings of student including high category that 63,7%. Of the three indicators that obtained of description of the class XI student interestÂ  in the subject of decorating fashion is quite that 59,2%. Keywords: Interest study Students, Decorate Fashion